Pengaruh Brand Image dan Social Media Marketing Terhadap Loyalitas Konsumen dengan Kepuasan Pelanggan Sebagai Variabel Mediasi : Studi Kasus pada Konsumen Wijaya Hijab (Lembaga Pengembangan Kinerja Dosen, 2025)
This study explores the influence of brand image and social media marketing on consumer loyalty, with customer satisfaction serving as a mediating variable, focusing on Wijaya Hijab as the research object. As digital platforms become crucial in marketing strategies, social media marketing plays a significant role in engaging Millennial and Generation Z consumers. Using a quantitative approach, data were collected through questionnaires from 221 respondents, employing Structural Equation Modeling (SEM) via IBM AMOS 26 for analysis. The findings reveal that brand image positively affects customer satisfaction, which in turn significantly enhances consumer loyalty. However, social media marketing, while showing a direct positive impact on consumer loyalty, does not significantly influence customer satisfaction. The mediating effect of customer satisfaction between brand image and loyalty is confirmed, whereas it is not supported between social media marketing and loyalty. These results suggest that while an established brand image contributes to increased satisfaction and loyalty, social media marketing directly fosters loyalty without necessarily increasing satisfaction. For practical implications, the study advises Wijaya Hijab and similar Islamic fashion SMEs to strengthen brand image alongside social media engagement to enhance customer loyalty effectively. This research adds to the growing evidence of digital marketing's nuanced impacts on consumer behavior in the Muslim fashion industry.